The Impact of Dementia's Affiliate Stigma on the Mental Health of Relatives: A Cross Section Survey - Van den Bossche, Pauline; Schoenmakers, Birgitte (Frontiers in Psychology, 2022)
Objective To determine the impact of the affiliate stigma on mental well-being of relatives caring for a person with dementia. Design The study was conducted in a cross sectional design. Setting The study was conducted in a public setting, addressing relatives caring for a person with dementia. Participants Participants were relatives of patients with a formal diagnosis of dementia. Relatives were defined as caring or living closely to a patient. Participants were recruited with the help of care and welfare organizations. Outcome Measures The main outcome measure was the impact of the affiliate stigma on mental well-being of caring relatives. Results 228 participants fully completed the survey. Women, relatives with a higher education and partners experienced more impact of the affiliate stigma on mental well-being than man, relatives with a lower education and relatives with another relationship to the person with dementia (resp. F-ratio = 15.67; p = 0.0001; F-ratio = 2.5865; p = 0.0381; F-ratio = 3.1131; p = 0.0099). The duration of dementia and the age of the caregiver had a clear significant effect on affiliate stigma (F-ratio = 4.9104; p = 0.0083) (F-ratio = 6.5515, p = 0.0112). Conclusion This study revealed that caregiver related features are predicting the presence of an affiliate stigma. Interventions to prevent or reduce the impact of this stigma might focus on these groups. Education about dementia and the impact on patients, relatives and the broader social context might alter the affiliate stigma surrounding dementia.